Variety of Tank Colours to Enhance the Colour Quality of Platyfish (Xyphophorus helleri) - Ina Oktaviani; Muhammad Junaidi; Bagus Dwi Hari Setyono (Jurnal Biologi Tropis, 2020)
One of the factors that affect the colour quality of the platy fish (Xyphophorus helleri) during cultivation is the environment in bright light conditions, where setting bright light conditions can be done using a tank with a colour that can absorb light. Therefore, a study was conducted to examine the effect of tank colour on improving the colour quality of the platy fish and determining the correct tank colour. This research was conducted with an experimental method using a completely randomized design (CRD) consisting of five treatments repeated three times. The colour treatments of the tanks used were white, black, red, orange and yellow. The parameters observed were the increase in colour, growth in absolute weight and length and survival rate of platy fish. The results showed that the use of different tank colours had a significant effect (p <0.05%) on the improvement of colour quality and growth in absolute weight, and had no significant effect (p> 0.05) on absolute length growth and survival rate. The highest increase in colour quality was in white tanks with brightness values ranging from 13-15% and absolute weight growth ranging from 0.21 to 0.25 g. Therefore, in the cultivation of platy fish, a white tank should be used.